Combination of transcriptomic and proteomic approaches helps unravel the mechanisms of luteolin in inducing liver cancer cell death via targeting AKT1 and SRC - Ma, Junxia; Mo, Jinggang; Feng, Yifu; Wang, Liezhi; Jiang, Hao; Li, Junmin; Jin, Chong (Frontiers in Pharmacology, 2024)
Luteolin, a natural compound commonly used in traditional Chinese medicine, shows clinical potential as an anti-liver cancer agent. The mechanisms underlying the anti-liver cancer effect of luteolin are limited versus those reported for other cancers.Accordingly, this study was conducted to bridge the existing knowledge gap. Transcriptomic and proteomic analyses of the response of the hepatocellular carcinoma cell line HuH-7 to luteolin were conducted, and a possible pathway was elucidated using confocal laser scanning microscopy (CLSM), flow cytometry, and bio-layer interferometry assay to systematically explore the possible mechanisms underlying the inhibition of the proliferation of liver cancer cells by luteolin. Results showed that luteolin significantly inhibited HuH-7 cell proliferation. Transcriptomic and proteomic analyses collectively revealed that luteolin could promote cell cycle arrest and apoptosis in HuH-7 cells through transcription factors p53, nuclear factor kappa B (NF-κB), FOXO, ATF2, and TCF/LEF via AKT1, as well as the KEAP-NRF and SRC-STAT3 pathways. Furthermore, AKT1 and SRC were identified as the 2 targets of luteolin. Nuclear translocation of transcription factors p53 and NF-κB were affected by luteolin administration. Additionally, AKT1 activity affected normal metabolism in HuH-7 cells and resulted in the accumulation of reactive oxygen species, which activated MOMP and further promoted apoptosis. Our results systematically elucidate the mechanism of luteolin in inhibiting the proliferation of liver cancer cells, mainly through cell cycle arrest and apoptosis via targeting AKT1 and SRC.